Biot's problem for a Biot material. (December 2015) - Selvadurai, A.P.S.; Shi, Li
Abstract: The paper presents a solution to the problem of an infinite beam of finite width resting on a poroelastic subgrade. The basic concepts of the elasticity solution are reviewed and the formulation is extended to consider the interaction between the infinite beam and a Biot poroelastic halfspace. A combination of Fourier and Laplace transforms are used to solve the problem. The influence of adhesion and drainage effects is accounted for by considering bounding techniques for prescribing the boundary conditions on the interface. The results of the analytical solution are used to validate the accuracy of a computational approach that uses a standard multi-physics scheme.